A meta-ethnography of participatory health research and co-production in Nepal. (May 2022) - Yoeli, Heather; Dhital, Ranjita; Hermaszewska, Susannah; Sin, Jacqueline
Abstract: As global health research seeks to decolonialise, democratise, and become more culturally engaging, researchers are increasingly employing participatory and co-productive methods. Working from post-structural perspectives, this meta-ethnographic review explores how such health research in Nepal engages with the epistemological, methodological, and ethical questions it encounters. Five databases including Nepali NepJOL were searched for studies from inception to March 2021. The review included seven studies covering women's group co-production, interviews guided by photo-elicitation, observational methods to explore maternal and child health, mental health, and environmental determinants of health. This meta-ethnography identified that, against the background of a pluralist heritage of health practices, global collaborations involving Nepali researchers and practitioners used participatory research methodology to work with the local populations to improve health and co-production seek primarily to promote Western biomedical and psychosocial interventions. Both advantages and disadvantages were acknowledged. Empirical verification and global acceptance of Western biomedical and psychosocial knowledge were seen as beneficial. Moreover, Western biomedicine was perceived by some as more effective than some local practices in improving health; nevertheless, Nepal faces many challenges that neither can address alone. For participatory and co-productive approaches to become epistemologically enculturated within Nepali health research, researchers need to co-develop more local models and methods which are culturally sensitive and appropriate. Meaningful and effective participatory research can promote active involvement of people who deliver as well as people who use the community-based health care support. These are crucial to optimise sustainable change that global health research partnerships set out to achieve. This meta-ethnography recommends that researchers engage at a deeper level with the epistemological differences between themselves and the communities with whom they seek partnership. Cross-cultural research teams should discuss and address the power differentials which might affect them. Research highlights: Participatory health research and co-production are increasingly popular in Nepal. Participatory methods often seek to introduce a biomedical worldview to communities. Nepali communities welcome most forms of research which improve their health. When power differentials are unacknowledged, research may perpetuate colonialism. Post-structural meta-ethnography can address power differentials in global research.